Pengaruh Penerapan Ukuran Huruf Ergonomis Pada Papan Tulis Terhadap Kelelahan Visual dan Kelelahan Intelektual Siswa Sekolah Dasar “X” di Sleman Tahun 2013 - Afifah Nulaila Desi Wijayanti; Muryoto Muryoto; Rizki Amalia (Poltekkes Kemenkes Yogyakarta, 2014)
The rate of incidence due to visual impairment in children is very high. Meanwhile, educational facilities and infrastructures which are not ergonomic can be one of the triggers of the onset of visual fatigue and intellectual fatigue among students. The size of letters written on chalkboards in the classrooms should be adjusted to students who sit farthest. Based on a preliminary survey conducted in Elementary School “X” in Sleman, it was found that 7,2 % of students have already worn glasses, and 7 out of 10 of normal eye students were complaining some things related with eye tiredness. The study was aimed to know the influence of the application of ergonomical size letters on the chalkboard toward the visual fatigue and intellectual fatigue among students of Ele-mentary School “X” by conducting a true experiment which followed pre-test post-test with control group design. From all grade IV and V students of the school, 80 were sampled randomly as the respondents and then they were divided equally into two groups as the treatment and control ones. Fifteen minutes prior to and after a 35 minutes duration learning activities, all respondents filled in the questionnaire of visual fatigue and Bourdon Wiersma test. In the treatment group, students were asked to read script written on the chalkboard by using ergonomic letters; mean-while in the control group, the written letter were followed the usual size used by the teachers. The study data which were analysed by independent t-test at 95 % significancy level, showed results that students in the treatment group had significantly lower visual and intellectual fatigue, com-pared with those of students in the control group (all p values <0,001). To help students in the learning process, teachers of the elementary school are advised to change their habit in writing letters in the chalkboards with minimal size of 3,75 cm.